Experimental analysis of the dielectrophoretic forces influence on height of rise of fluid in a capillary system for boiling control in micro-channel - Lackowski, Marcin; Karwacki, Jarosław (Advances in Mechanical and Materials Engineering, 2017)
Flow control in microchannels is one of the key issues in many areas of modern technology, such as medicine, bio-engineering, chemistry and, in recent years, also in problems of thermodynamic processes control. This paper presents the results of experimental studies on the dynamics of liquid movement between the walls of a microchannel, which is the effect of the electric field applied to the walls (the dielectrophoresis phenomenon). The presented results fill a gap in the literature, being also an important material for the determination of the device key parameters, such as the height of the microchannel electrodes, frequency and amplitude of applied voltage, the selection of periods with and without voltage, all of which affect the operation of the device.